Freedoms in the Hungarian April Laws of 1848 - Gergely Gosztonyi (Journal on European History of Law, 2024)
The French Revolution and the changes in Europe in the first half of the 19th century increasingly called into question the caste order, under which only a small percentage of society could enjoy freedoms, including not only political but also private and criminal rights. Based on Western European ideas followed by the legal fight of brave Hungarians, in 1848, Hungary almost got its constitution in the form of 31 Acts, called the Hungarian April Laws. Among others, those Acts consisted of the issues of equality of rights, political rights, freedom of the press, freedom of religion and academic freedom. Freedoms that, after the Austro-Hungarian Compromise, the Hungarian Parliament went back to and built a reform era on.